(untitled) (Don Bosco Institute of Technology Delhi Journal of Research, 2025)
This research aims to investigate the processes for using digital finance to address the sustainability triple-bottom-line challenge, as digital finance is essential for attaining sustainability. Within the context of digital finance, this article investigates the inner workings of the relationship between financial performance and ESG (environmental, social, and governance) factors. Indirectly improving both short- and long-term financial success for organizations, digital finance promotes ESG performance, according to the research. Furthermore, the key enabler for ESG and short-term financial success is the depth of digital finance adoption. According to the results of the mechanism study, improving green innovation and bolstering digital transformation would strengthen the favorable correlation between digital finance and ESG. Furthermore, according to heterogeneity study, big businesses and SOEs (state-owned enterprises) have a stronger positive effect on ESG and financial performance when it comes to digital finance use depth, but small firms and non-SOEs have a stronger positive effect on ESG when it comes to coverage breadth. By outlining potential avenues for sustainable behavior, this article deepens our understanding of digital money.